(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
Colour has always been of great importance in the life of a person. We cannot imagine the life without colour. This article aims at comparing phraseological units which contain elements of colour designation in English and Karakalpak languages. Emphasis is done on the analysis of theoretical data on the subject; determining the role and meaning of phraseological units in the English language. The author has considered colour as a component of the cultural connotation of phraseological units, has classified and disclosed the meaning of phraseological units with a colour designation component. This article includes some examples of English phraseological units which have equivalents in Karakalpak language.